2017
DOI: 10.18203/issn.2454-5929.ijohns20170931
|View full text |Cite
|
Sign up to set email alerts
|

Aetiological factor for chronic suppurative otitis media: a retrospective study

Abstract: <p class="abstract"><strong>Background:</strong> Otitis media (OM) refers to a group of complex infectious and inflammatory diseases affecting the middle ear. The present study was conducted to understand the various aetiological factors in chronic suppurative otitis media (CSOM) and also to take into possible hereditary factors<span lang="EN-IN">. </span></p><p class="abstract"><strong>Methods:</strong> This retrospective study was conducted in 150 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…15 We observed that the disease is more prevalent in males than females which is similar to other studies done in Singapore, Pakistan, Iran and other parts of India. 16 Siraj et al in his study reported that the prevalence of CSOM was found to be slightly higher in male children than female. 17 Islam in 2007, in his study revealed that the male to female ratio regarding the prevalence of the disease is much higher.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…15 We observed that the disease is more prevalent in males than females which is similar to other studies done in Singapore, Pakistan, Iran and other parts of India. 16 Siraj et al in his study reported that the prevalence of CSOM was found to be slightly higher in male children than female. 17 Islam in 2007, in his study revealed that the male to female ratio regarding the prevalence of the disease is much higher.…”
Section: Discussionmentioning
confidence: 89%
“…18 Our study showed that COM is more common in rural population especially affecting the lower socio-economic strata, which is quite similar to a study made by Okafor et al who stated that the majority of the patients with chronic ear disease came from poor communities living in subsistence agricultural or slum areas. 16 In a study conducted by Arunabha et al 60% of their patients were from low socio-economic class. Poor living conditions, poor access to medical care, inadequate medical treatment, recurrent upper respiratory tract infections, nasal diseases have been recognized as risk factors for COM.…”
Section: Discussionmentioning
confidence: 96%